Menyoal relevansi tafsir visual: Analisis penafsiran akun @Quranreview terhadap QS. Muhammad ayat 9 - Nastiar, Muhammad Addien (Maliki Interdisciplinary Journal, 2023)
Al-Quran interpretations are generally presented textually in commentary books written by mufassirs, from the classical era to the contemporary era. The role of the internet in this era is crucial, the Instagram account Quranreview exists as a creator who always associates trends with verses of the Koran which are considered to correlate with these trends. Quranreview often associates the title text with trends or trend contexts with verses of the Koran. This study will use a qualitative method with a critical discourse analysis approach through a combination of text analysis and context analysis. There is research to see the validity of the correlation between the trend and the content of the interpretation presented by the Quranreview account, and as an effort to arouse the interest of experts to pay attention to the existence of visual interpretations that are scattered on social media. Interpretations of the Koran which so far have only been listed in books can be visualized attractively, so that the interpretations of the Koran can be understood easily and by spreading visual interpretations on social media, it can attract the interest of ordinary people to understand the meanings contained in them. Al-Quran in a simple, attractive, and easy.